The evaluation of the serum brain natriuretic peptide concentrations in preeclamptic and healthy pregnant women and its potential relationship with mean arterial blood pressure - Yücedağ, Mehtap; Yılmaz, Özgür; Kırteke, Kenan; Özün Özbay, Pelin; Küme, Tuncay (Perinatal Journal, 2020)
Objective In this study, we aimed to investigate the correlation between serum brain natriuretic peptide (BNP) concentrations and blood pressure levels by comparing serum brain natriuretic peptide (BNP) concentrations in preeclamptic and normotensive pregnant women and to assess its potential role in the preeclampsia pathogenesis. Methods A total of 48 preeclamptic and 39 normotensive patients were included in the study prospectively. Systolic diastolic and mean arterial blood pressure of the pregnant women were measured. Serum BNP concentrations were measured by enzyme immunoassay method. The variable differences between the groups were analyzed by independent samples t-test. Potential correlations between the variables were assessed by Pearson’s correlation analysis. Results There was no difference between the groups in terms of age (26.18±11.49 years vs. 26.04±14.06 years), gestational age (31.59± 6.94 weeks vs. 30.17±5.72 weeks), parity (2.62±1.4 vs. 2.53±1.82) and body mass index (30.71±16.33 kg/m2 vs. 30.09±13.82 kg/m2) (p>0.05). Systolic (148.66± 61.82 mmHg vs. 126.44±97.47 mmHg; p=0.015), diastolic (81.19±52.25 mmHg vs. 97.29±14.27 mmHg; p=0.019) and mean arterial pressure (113.97±41.76 mmHg vs. 96.26±27.25 mmHg; p<0.001) levels were higher in the pregnant women complicated with preeclampsia. In addition, serum BNP concentrations were also higher in the preeclamptic pregnant women than the control group (139.42±62.19 pg/mL vs. 99.28±19.32 pg/mL; p=0.028). BNP levels were significantly associated with only mean arterial pressure (b=0.241, p=0.037). Also, there was a significant positive correlation between BNP levels and mean arterial pressure (r=0.406, p=0.002). Conclusion We recommend further prospective studies with wider populations to assess whether BNP levels, which increase in preeclampsia, are associated with blood pressure levels or not.